LANGUAGE OF PRIMARY SCHOOL STUDENTS FORMATION OF LEARNING ABILITIES INNOVATIVE METHODS - Saminjonova, Zuxraxon Xusanboy qizi (INTERNATIONAL CONFERENCES, 2022)
This article discusses innovative ways to shape the language skills of primary school students and the role and importance of dictionaries in this process.